(untitled) (Revista Latino-Americana de Enfermagem, 2024)
Objective: this study aimed at estimating and comparing the reliability of temperature measurements obtained using a peripheral infrared temporal thermometer, a central cutaneous thermometer (“Zero-Heat-Flux Cutaneous thermometer”) and an esophageal or nasopharyngeal thermometer among elective surgical patients in the intraoperative period. Method: a longitudinal study with repeated measures carried out by convenience sampling of 99 patients, aged at least 18 years old, undergoing elective abdominal cancer surgeries, with anesthesia lasting at least one hour, with each patient having their temperature measured by all three methods. Results: the intraclass correlation coefficient showed a low correlation between the measurements using the peripheral temporal thermometer and the central cutaneous (0.0324) and esophageal/nasopharyngeal (-0.138) thermometers. There was a high correlation (0.744) between the central thermometers evaluated. Conclusion: the data from the current study do not recommend using infrared temporal thermometers as a strategy for measuring the body temperature of patients undergoing anesthetic-surgical procedures. Central cutaneous thermometers and esophageal/nasopharyngeal thermometers are equivalent for detecting intraoperative hypothermia.